Anti-HIV-1 activity of trichobitacin, a novel ribosome-inactivating protein - Zheng Yong-Tang; Ben Kun-Long (Acta Pharmacologica Sinica; Vol 21, No 2 (February 2000): Acta Pharmacologica Sinica, 2016)
"AIM: To determine whether trichobitacin, a novel ribosome-inactivating protein purified from the root tubers of Trichosanthes kirilowii, possesses the anti-HIV activity. METHODS: The inhibition of syncytial cell formation induced by human immunodeficiency virus type 1 (HIV-1) was determined under microscope, reduction of HIV-1 p24 antigen expression level was measured by ELISA, and decrease in numbers of HIV-1 antigen positive cells in acutely and chronically infected cultures were detected by indirect immunofluorescence assay. RESULTS: Trichobitacin was found to greatly suppress syncytial cell formation induced by HIV-1 and to markedly reduce both expression of HIV-1 p24 antigen and the number of HIV antigen positive cells in acutely but not chronically HIV-1 infected culture. The median inhibitory concentration (IC50) in inhibition of syncytial cell formation and HIV antigen positive cells were 5 micrograms.L-1 (95% confidence limits: 1.3-20 micrograms.L-1) and 0.09 mg.L-1 (95% confidence limits: 0.011-0.755 mg.L-1), respectively. CONCLUSION: Trichobitacin is a novel ribosome-inactivating protein with anti-HIV-1 activity."